Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio on postoperative day three as a biochemical predictor of clinically significant pancreatic fistula in patients undergoing distal pancreatectomy - G.E. Sánchez-Morales; J. Cisneros-Correa; D. Lanzagorta-Ortega; R.H. Pérez-Soto; I. Domínguez-Rosado; C. Chan (Revista de Gastroenterología de México (English Edition), 2024)
Introduction and aims: Distal pancreatectomy is a frequent procedure and postoperative fistula, its most common complication, has an incidence of 30 to 60%. The aim of the present work was to study the role of the neutrophil-to-lymphocyte ratio and the platelet-to-lymphocyte ratio, as indicators of inflammatory response in the setting of pancreatic fistula. Methods: A retrospective observational study was conducted on patients that underwent distal pancreatectomy. The diagnosis of postoperative pancreatic fistula was made according to the definition proposed by the International Study Group on Pancreatic Fistula. The relation of postoperative pancreatic fistula to the neutrophil-to-lymphocyte ratio and the platelet-to-lymphocyte ratio was determined in the postoperative evaluation. SPSS v.21 software was utilized for the statistical analysis and a P<.05 was considered statistically significant. Results: A total of 12 patients (27.2%) developed grade B or grade C postoperative pancreatic fistula. ROC curves were constructed and a threshold of 8.3 (PPV 0.40, NPV 0.86) was established for the neutrophil-to-lymphocyte ratio, with an area under the curve of 0.71, sensitivity of 0.81, and specificity of 0.62, whereas a threshold of 33.2 (PPV 0.50, NPV 0.84) was established for the platelet-to-lymphocyte ratio, with an area under the curve of 0.72, sensitivity of 0.72, and specificity of 0.71. Conclusion: The neutrophil-to-lymphocyte ratio and the platelet-to-lymphocyte ratio are serologic markers that can aid in identifying patients that will present with grade B or grade C postoperative pancreatic fistula, thus helping to provide an opportune focus on care and resources. Resumen: Introducción y objetivos: La pancreatectomía distal es un procedimiento frecuente y la fístula postoperatoria, su complicación más frecuente tiene una incidencia del 30 al 60%. El objetivo de este trabajo fue estudiar el papel de la relación neutrófilos/linfocitos y la relación linfocitos/plaquetas como indicadores de respuesta inflamatoria en el escenario de la fístula pancreática. Métodos: Este trabajo es un estudio observacional retrospectivo que incluye pacientes que fueron sometidos a pancreatectomía distal. El diagnóstico de fístula pancreática postoperatoria se estableció según la definición del Grupo Internacional de Estudio de Fístula Pancreática (ISGPF, por sus siglas en inglés). La asociación entre fístula pancreática posoperatoria, la relación neutrófilos/linfocitos y la relación plaquetas/linfocitos fue determinada en la evaluación posoperatoria. Se utilizó el software SPSS® v.21 para el análisis estadístico y un valor de p inferior a 0.05 se consideró estadísticamente significativo. Resultados: Un total de 12 pacientes (27.2%) desarrollaron fístula pancreática postoperatoria (POPF, por sus siglas en inglés) grado B o C. Se construyeron curvas ROC y se estableció un umbral de 8.3 (VPP: 0.40; VPN: 0.86) para la relación neutrófilos/linfocitos con un área bajo la curva de 0.71, sensibilidad de 0.81 y especificidad de 0.62; por su parte, para la relación plaquetas/linfocitos se estableció un umbral de 33.2 (VPP: 0.50; VPN: 0.84), con un área bajo la curva de 0.72, sensibilidad de 0.72 y especificidad de 0.71. Conclusión: La relación neutrófilos/linfocitos y la relación plaquetas/linfocitos son marcadores serológicos que pueden ayudar a identificar a pacientes que presentarán fístula pancreática postoperatoria grado B o C, y así ayudar a enfocar la atención y los recursos de manera oportuna.